Associations between wheelchair user`s shoulder pain index and tendinitis in the long head of the biceps tendon among female wheelchair basketball players from the Japanese national team - Tsunoda, K.; Mutsuzaki, H.; Kanae, K.; Tachibana, K.; Shimizu, Y.; Wadano, Y. (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2021)
Background: Among injuries in wheelchair athletes, shoulder injury is the most common. An easy and valid assessment tool is required to monitor the shoulder status in wheelchair athletes anytime. The present study aimed to investigate the association of wheelchair user`s shoulder pain index (WUSPI) with physical examinations for tendinitis in the long head of the biceps tendon (LHBT) and range of motion (ROM) of shoulder movements among female wheelchair basketball players from the Japanese national team. Methods: A total of 21 female players (mean age, 32.0 ± 7.9 years) participated in this study. LHBT tendinitis was assessed using findings of tenderness in the bicipital groove point (TBGP) and speed test. Shoulder ROMs were evaluated in three movements—namely, abduction, flexion, and extension. Results: The mean total WUSPI score was 9.55 ± 13.35 points. The players were more likely to experience shoulder pain during activities related to wheelchair pushing and object lifting. A higher total WUSPI score was strongly and moderately associated with positive findings of TBGP (effect size r = 0.82) and speed test (r = 0.49), respectively. Furthermore, the total WUSPI score was significantly associated with limited ROM in shoulder abduction (r = 0.47) and flexion (r = 0.43). Receiver operating characteristic analysis showed that the total WUSPI score had a significant area under the curve (AUC) for positive findings of TBGP (AUC = 0.98), speed test (AUC = 0.83), and limited ROM in abduction (AUC = 0.84). When optimal cut-points were set by the Youden index, total WUSPI scores of 4.1 points (sensitivity = 1.00, specificity = 0.92), 11.3 points (sensitivity = 0.80, specificity = 0.81), and 3.3 points (sensitivity = 1.00, specificity = 0.65) were recommended for screening positive findings of TBGP, speed test, and limited ROM in abduction, respectively. Conclusion: TBGP, which is a major finding of LHBT tendinitis, was strongly associated with the total WUSPI score in physical examinations. Hence, pain assessed by WUSPI could reflect the presence of LHBT tendinitis. The WUSPI is a superior tool for monitoring the shoulder status of wheelchair basketball players.